Identifying age-friendly behaviours for bus driver age-awareness training - Broome, K.; Worrell, L.; Fleming, J.; Boldy, Duncan (Canadian Association of Occupational Therapists, 2011)
Background. Occupational therapists may be involved in advocating for age-friendly bus systems and training bus drivers in age-awareness. In order to develop evidence-based bus driver age-awareness training programs, the specific required bus driver behaviours should be explicated. Purpose. This study aims to define, clarify, and illustrate behaviours associated with bus driver friendliness and helpfulness. Methods. Forty older people (aged 60 and over) in Queensland, Australia, completed a round trip bus journey and subsequent interview. Qualitative content analysis of participant observations with stimulated recall interviews was used to identify categories and themes around friendly and helpful bus drivers. Findings. General professional behaviours included making older people feel safe, courtesy, friendliness, helpfulness and being aware of invisible disabilities and specific professional behaviours included giving time, pulling in close to the curb, communication, and information. Implications. The findings are incorporated into suggestions for a bus driver age-awareness training program.